LEGISLACION PARA EL ACCESO A LA JUSTICIA EN PERSONAS CON DEUDAS ALIMENTARIAS EN EL MARCO DE PROCESOS DE REDUCCION ALIMENTARIA - CHIRINOS ARROYO, ASIS VIVIANO (2020)
Justice as a moral principle, forms one of the most important foundations within a trial. For this reason, it is important to enforce this right to the citizen who makes a demand concerning the process of food reduction since in Article 565-A, which is found in the Civil Procedure Code, an approach is shown that prevents putting Practice this process. In the present work it is proposed to modify such article, exclusively in the situation in which the citizen who makes the demand, undoubtedly, certifies that for justified reasons he is not up to date with said duty. Among those causes are the absence of economic income, physical impediments that arose; and, in the case of loss of liberty. When requesting an anticipated reduction of food, it can be seen that equality with justice is directly violated, since this request is not evaluated and much less granted. For this reason, it is considered to use the one established in Article 674 of the Civil Procedural Code, where measures related to the problem are established; as long as it is verified that the one who makes the demand reliably is in the situations already mentioned. In order not to abuse that right, a way was established to establish periods for the breach of that duty, marking three months as the deadline, in which the defendant and the plaintiff can justify and demonstrate the current situation. Finally, it is clear that it does not violate the interests of the child, so that the integrity of the child will always be safeguarded, in any situation that affects and violates their rights, which will require compliance with the corresponding maintenance payment, evaluating the current reality of the defendant.